Religious and Customary Perspectives on the Transition Process of Guardians in Malojongkon Boru Marriage Practices - Hasibuan, Ahmad Ridoan; Yazid, Imam; Firmansyah, Heri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
One of the most common issues in marriage is the marriage contract, which might take days to finalize. It happens when a guardian refuses to marry off his daughter because he disapproves of the marriage. Therefore, Malojongkon Boru is frequently practiced to get the approval of the woman's guardian or father. The subject of discussion for this study is the transition of the nasab guardian to the judge guardian in the practice of Malojongkon Boru. The focus of the problem in this study is the perspective of Indonesian Ulema Council (MUI) and Traditional Leaders on the transition of nasab guardian to the judge guardian in Malojongkon Boru marriage practice. This study is a field research with a qualitative approach. The data sources are classified into field data as primary data, including interviews and documentation, and literature data as secondary data. The findings indicate that MUI and Traditional Leaders view the transition of marriage guardians in the practice of Malojongkon Boru marriage as conducted in conformity with Islamic law.